Overview of Reticulocyte Counts in Patients with Chronic Kidney Failure at Ciamis Regional General Hospital - Atun Farihatun; Doni Setiawan; Dallya Mentari (LPPM STIKes Muhammadiyah Ciamis, 2025)
Background & Objectives: The prevalence of chronic kidney failure in Ciamis Regency based on medical records data from Ciamis Regional General Hospital in 2023 was 318 patients. Chronic kidney failure often causes complications, one of which is anemia. Reticulocyte examination in patients with chronic kidney failure can help diagnose complications such as anemia and determine the response to bone marrow. The purpose of this study was to determine the number of reticulocytes in patients with chronic kidney failure. Method: This research method is descriptive with purposive sampling technique. The respondents in this study were 39 people with chronic kidney failure at Ciamis Regional General Hospital. This study was conducted at the Hematology Laboratory of STIKes Muhammadiyah Ciamis in May 2024. The examination technique was carried out using brilliant crystal blue solution staining and examined under a microscope. The examination results were compiled into tables and explained narratively. Results: The results of this examination showed that 34 people (87%) had normal reticulocyte counts and 5 people (13%) had above-normal reticulocyte counts. Conclusion: It can be concluded that the average reticulocyte count in patients with chronic kidney failure is normal.